Mesoporous Manganese Oxide Nanowires for High-Capacity, High-Rate, Hybrid Electrical Energy Storage - Yan, Wenbo; Ayvazian, Talin; Kim, Jungyun; Liu, Yu; Donavan, Keith C; Xing, Wendong; Yang, Yongan; Hemminger, John C; Penner, Reginald M (ACS nano, 2011)
Arrays of mesoporous manganese dioxide, mp-MnO2, nanowires were electrodeposited on glass and silicon surfaces using the lithographically patterned nanowire electrodeposition (LPNE) method. The electrodeposition procedure involved the application, in a Mn(ClO4)2-containing aqueous electrolyte, of a sequence of 0.60 V (vs MSE) voltage pulses delineated by 25 s rest intervals. This “multipulse” deposition program produced mp-MnO2 nanowires with a total porosity of 43–56%. Transmission electron microscopy revealed the presence within these nanowires of a network of 3–5 nm diameter fibrils that were X-ray and electron amorphous, consistent with the measured porosity values. mp-MnO2 nanowires were rectangular in cross-section with adjustable height, ranging from 21 to 63 nm, and adjustable width ranging from 200 to 600 nm. Arrays of 20 nm × 400 nm mp-MnO2 nanowires were characterized by a specific capacitance, C sp, of 923 ± 24 F/g at 5 mV/s and 484 ± 15 F/g at 100 mV/s. These C sp values reflected true hybrid electrical energy storage with significant contributions from double-layer capacitance and noninsertion pseudocapacitance (38% for 20 nm × 400 nm nanowires at 5 mV/s) coupled with a Faradaic insertion capacity (62%). These two contributions to the total C sp were deconvoluted as a function of the potential scan rate.